The Effect Waste Ceramic Tile as Partial Material Replacement of Sand for Sand Cement Brick - Mohd Anuar, Nur Amira; Jamaluddin, Norwati (Recent Trends in Civil Engineering and Built Environment, 2024)
The production of sand cement bricks is now focused on the use of waste materials as a substitute for some of the materials in bricks especially sand. The application of recycled materials in the construction industry is essential for the sustainable development of the country. Waste ceramic tiles are used as a semi-sand substitute material in sand cement bricks because 30% of the daily production of the ceramic industry is estimated to be wasted. In this study, the performance of bricks was investigated based on mechanical and physical tests. The percentage of residual replacement of ceramic tiles in sand cement bricks is 0%, 10%20%, and 30%. From the analysis, the ceramic tile residue contributes to the improvement of the mechanical and physical properties of the brick. Significant findings from this test, it can be seen that among the samples, bricks with 30% substitution had the greatest strength of 61N/mm on the 28th day which is directly proportional to the brick density from the test conducted. From the water absorption test, the brick is classified as a first-class brick because the average water absorption obtained is below 15%. These bricks are categorized as hard bricks because no trace is left on the surface of the brick when conducting the hardness test as well as not breaking after the impact test is carried out.